2023
DOI: 10.3390/ijms24021016
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriobiota of the Cave Church of Sts. Peter and Paul in Serbia—Culturable and Non-Culturable Communities’ Assessment in the Bioconservation Potential of a Peculiar Fresco Painting

Abstract: The principal aim of this study was to determine bacterial diversity within the Cave Church of Sts. Peter and Paul, via culturable and non-culturable approaches, and elucidate the antifungal potential of autochthonous antagonistic bacterial isolates against biodeteriogenic fungi. Furthermore, whole-genome sequencing of selected bacterial antagonists and the analysis of genes included in the synthesis of secondary metabolites were performed. With the highest RA values, determined in metabarcoding analysis, phyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…Methylocella, Methylovirgula and Mycobacterium) strains were promoted by warmer and humid climatic conditions (lower MDR/TSEA and/or higher AI/PSEA/MAP). Conversely, some phototrophic (Cyanobacteria and Roseiflexus) and rock weathering (Rubrobacter and Actinomycetospora) bacterial genera were positively associated with higher arid conditions (Saiz-Jimenez, 2012;Farda et al, 2022;Dimkić et al, 2023). In light of this, we would propose that climatic variation represents one of the main epistatic drivers in determining the energetic status of caves and the assembling of microbial community cores.…”
Section: Discussionmentioning
confidence: 93%
“…Methylocella, Methylovirgula and Mycobacterium) strains were promoted by warmer and humid climatic conditions (lower MDR/TSEA and/or higher AI/PSEA/MAP). Conversely, some phototrophic (Cyanobacteria and Roseiflexus) and rock weathering (Rubrobacter and Actinomycetospora) bacterial genera were positively associated with higher arid conditions (Saiz-Jimenez, 2012;Farda et al, 2022;Dimkić et al, 2023). In light of this, we would propose that climatic variation represents one of the main epistatic drivers in determining the energetic status of caves and the assembling of microbial community cores.…”
Section: Discussionmentioning
confidence: 93%
“…This order has previously been identified in samples obtained from a fresco painting inside the Cave Church of the Sts. Peter and Paul [48]. In addition, it has been observed that bacteria of this order, which are capable of withstanding stressful conditions, have demonstrated improved functional pathways related to the metabolism of amino acids and carbohydrates [49].…”
Section: Description Of the Biodiversity Of Prokaryotic Microorganism...mentioning
confidence: 99%
“…and Achromobacter xylosoxidans NUU2, where B. subtilis NUU4 had signi cant plant growth promotion capabilities, improved rhizobia symbiosis, and reduced the infection rate of root rot caused by F. solani. It is a biocontrol strategy in which the control agent consumes nutritional resources before the pathogen, which is advantageous when the fungus grows quickly and covers a large area; nutrient and space competition is one proposed inhibition mechanism for Aspergillus species suppression(Lahlali et al 2022;Dimkić et al 2023). Comparably, Sharma et al 2021 studied the diversity pattern and fungicidal activity of bacterial endophytes isolated from two different organic tomato varieties (V1 and V2).…”
mentioning
confidence: 99%